1991
DOI: 10.1002/jcp.1041470202
|View full text |Cite
|
Sign up to set email alerts
|

Altered cellular responses to serum mitogens, including platelet‐derived growth factor, in cultured smooth muscle cells derived from arteries of patients with moyamoya disease

Abstract: Progressive stenosis or occlusion of bilateral internal carotid arteries by fibrocellular intimal thickening results in cerebral ischemia in moyamoya disease. The etiology is unknown. We examined cultured arterial smooth muscle cells (SMC) from scalp arteries of five patients with moyamoya disease. In this study we investigated the responsiveness of the cells in culture to serum mitogens including platelet-derived growth factor (PDGF), a major mitogen of SMC, and compared the response to that of cells derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…25 vivo. Therefore, further study is necessary to elucidate the role of these growth factors in the pathogenesis of moyamoya disease.…”
Section: Resultsmentioning
confidence: 99%
“…25 vivo. Therefore, further study is necessary to elucidate the role of these growth factors in the pathogenesis of moyamoya disease.…”
Section: Resultsmentioning
confidence: 99%
“…When SMCs were cultured in MEM containing 10% FBS, the proliferation of HCSMC was significantly higher than that of HMSMC, as described previously. 10) For both HCSMC and HMSMC, the addition of 10% NRS produced a lower response compared with cells grown in MEM containing 10% FBS. In contrast, the cells cultured in MEM containing 10% QNYZS did not grow at all, even after 11 d (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…[6][7][8] The etiology of the disease remains unknown, but we have postulated that alterations in cellular responses to growth factors and cytokines in vascular cells are responsible for the development of intimal thickening in moyamoya disease. 10) We recently found that differences in the responses to platelet-derived growth factor and interleukin-1 in moyamoya SMCs are involved in the mechanism of intimal thickening in moyamoya disease. 9) In the present study, QNYZ and QNYZS showed inhibitory activities on the proliferation of moyamoya SMCs as well as control SMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight-week-old male Sprague-Dawley rats were obtained from the Experimental Animal Center of China Medical University. Primary RASMCs were prepared from the aortas of rats by the method previously described (18) and cultured in Dulbecco's modified Eagle's medium (DMEM, Gibco, Grand Island, NY) supplemented with 10% fetal bovine serum (FBS, Hyclone, Logan, UT), 2 mmol/l glutamine, 100 U/ml penicillin, and 100 µg/ml streptomycin at 37˚C in a humidified 5% CO 2 atmosphere. The purity of the cultured RASMCs was verified by immunostaining with a monoclonal antibody against smooth muscle-specific α-actin.…”
Section: Methodsmentioning
confidence: 99%